Biological roles of RNA m5C modification and its implications in Cancer immunotherapy - Song, Hang; Zhang, Jianye; Liu, Bin; Xu, Jing; Cai, Biao; Yang, Hai; Straube, Julia; Yu, Xiyong; Ma, Teng (Biomarker Research, 2022)
Epigenetics including DNA and RNA modifications have always been the hotspot field of life sciences in the post-genome era. Since the first mapping of N6-methyladenosine (m6A) and the discovery of its widespread presence in mRNA, there are at least 160-170 RNA modifications have been discovered. These methylations occur in different RNA types, and their distribution is species-specific. 5-methylcytosine (m5C) has been found in mRNA, rRNA and tRNA of representative organisms from all kinds of species. As reversible epigenetic modifications, m5C modifications of RNA affect the fate of the modified RNA molecules and play important roles in various biological processes including RNA stability control, protein synthesis, and transcriptional regulation. Furthermore, accumulative evidence also implicates the role of RNA m5C in tumorigenesis. Here, we review the latest progresses in the biological roles of m5C modifications and how it is regulated by corresponding “writers”, “readers” and “erasers” proteins, as well as the potential molecular mechanism in tumorigenesis and cancer immunotherapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 5-methylcytosine (m; cancer immunotherapy; Epigenetics; Non-coding RNAs; RNA methylation modification

Loss of IFN-gamma pathway gene expression in tumor cells as mechanism of immune escape of colorectal carcinoma - Britzen-Laurent, Nathalie; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Croner, Roland; Pilarsky, Christian; Merkel, Susanne; Stürzl, Michael (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22